(untitled) (LEGAL DIALOGICA, 2025)
This writing aims to: (1) to find out the form and process of an action in Combating Repeated Narcotics Crimes at the Makassar Police. (2) what are the obstacles experienced by the Makassar Police in the process of Combating Repeated Narcotics Crimes. The type of research used is empirical legal research. The research method used in writing this thesis is an empirical method, with secondary and primary data coverage, this research was conducted at the Makassar Police. The results of the writing show that the Role of Makassar Police Investigators in combating narcotics crimes has carried out procedures in accordance with Law Number 2 of 2002 concerning the Republic of Indonesia National Police, Law Number 8 of 1981 concerning Criminal Procedure Law (KUHP), and the Regulation of the Head of the Republic of Indonesia National Police (Perkap) related to the investigation of Criminal Acts. The obstacles experienced by the Makassar Police are the lack of human resources and the lack of security in the examination process so that those involved can easily escape their responsibilities. Writing Recommendations: All forms of obstacles experienced by law enforcement officers, in this case investigators, should be able to improve by recruiting human resources who have good standard competencies related to the rampant repeated narcotics crimes that occur in the community. Abstrak: Penulisan ini bertujuan untuk : (1) untuk mengetahui bentuk dan proses suatu tindakan dalam Penanggulangan Pengulangan tindak Pidana Narkotika di Polrestabes Makassar. (2) apa saja hambatan yang dialami oleh Polrestabes Makassar dalam proses Penanggulangan Pengulangan Tindak Pidana Narkotika. Tipe penelitian yang digunakan yaitu penelitian hukum empiris. Metode penelitian yang digunakan dalam penulisan skripsi ini adalah metode empiris, dengan cakupan data skunder dan primer, penelitian ini dilakukan di Polrestabes Makassar. Hasil penulisan menunjukkan bahwa Peran Penyidik Polrestabes Makassar dalam hal penanggulangan tindak pidana narkotika telah melakukan prosedur sesuai dengan Undang-undang Nomor 2 tahun 2002 Tentang Kepolisian Negara Republik Indonesia, Undang-Undang Nomor 8 Tahun 1981 Tentang Hukum Acara Pidana (KUHP), dan Peraturan Kepala Kepolisian Negara. Indonesia (Perkap) trkait penyidikan Tindak Pidana. Hambatan yang dialami oleh Polrestabes Makassar yaitu kurangnya SDM dan kurangnya pengaman dalam proses pemeriksaan sehingga dapat dengan mudah yang terlibat dapat lepas dari tanggung jawabnya. Rekomendasi Penulisan : Segala bentuk kendala yang dialami oleh aparat penegak hukum dalam hal ini Penyidik agar mampu berbenah sekiranya merekrut sumber daya manusia yang memiliki kompetensi standar yang baik terkait dengan maraknya tindak pidana Pengulangan Narkotika yang terjadi di lingkungan masyarakat.